Cortisol response marks biological sensitivity to kindergartners' social hierarchies for emerging school engagement. Issue 2 (15th February 2023) - Armstrong‐Carter, Emma; Bush, Nicole R.; Boyce, W. Thomas; Obradović, Jelena
Abstract: This longitudinal study investigated how kindergartners' position in the classroom social hierarchy and cortisol response relate to their change in school engagement across the first year of kindergarten ( N = 332, M = 5.3 years, 51% boys, 41% White, 18% Black). We used naturalistic classroom observations of social hierarchy positions, laboratory‐based challenges to elicit salivary cortisol response, and teacher, parent, and child reports of emotional engagement with school. Robust, clustered regression models revealed that in the fall, lower cortisol response (but not social hierarchy position) was associated with greater school engagement. However, by spring, significant interactions emerged. Highly reactive, subordinate children showed increases in school engagement from fall to spring of the kindergarten year, whereas highly reactive, dominant children showed decreases in school engagement. This is some of the first evidence that higher cortisol response marks biological sensitivity to early peer‐based social contexts.